2014
DOI: 10.1002/asia.201402201
|View full text |Cite
|
Sign up to set email alerts
|

Vertically π‐Expanded Imidazo[1,2‐a]pyridine: The Missing Link of the Puzzle

Abstract: The dehydrogenative coupling of imidazo[1,2-a]pyridine derivative has been achieved for the first time. In cases in which the most-electron-rich position of the electron-excessive heterocycle was blocked by a naphthalen-1-yl substituent, neither oxidative aromatic coupling nor reaction under Scholl conditions enabled the fusion of the rings. The only method that converted the substrate into the corresponding imidazo[5,1,2-de]naphtho[1,8-ab]quinolizine was coupling in the presence of potassium in anhydrous tolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 147 publications
0
12
0
Order By: Relevance
“…Thus, the spectra of both compounds are located in a similar spectral range, although the onset of the spectra of 3 is located at slightly higher energies than that of 2. Interestingly, the onset of the spectra of the reference compound 1 (19 050 cm À1 in absorption and 20 400 cm À1 in fluorescence) 12 is close to that of compounds 2 and 3. It can thus be concluded that p-expansion of imidazo[1,2-a]pyridine upon attaching a phenanthrene moiety, when compared with attaching a naphthalene moiety, does not contribute considerably to the energy separation between the ground and the lowest excited electronic singlet states.…”
Section: Spectroscopic and Kinetic Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…Thus, the spectra of both compounds are located in a similar spectral range, although the onset of the spectra of 3 is located at slightly higher energies than that of 2. Interestingly, the onset of the spectra of the reference compound 1 (19 050 cm À1 in absorption and 20 400 cm À1 in fluorescence) 12 is close to that of compounds 2 and 3. It can thus be concluded that p-expansion of imidazo[1,2-a]pyridine upon attaching a phenanthrene moiety, when compared with attaching a naphthalene moiety, does not contribute considerably to the energy separation between the ground and the lowest excited electronic singlet states.…”
Section: Spectroscopic and Kinetic Resultsmentioning
confidence: 61%
“…All of these show that prediction of properties of p-expanded imidazo[1,2-a]pyridines is not a trivial problem, and needs careful investigation, as has previously been done for hydrocarbons. 16 Suggestions for future studies A characteristic feature of both of the investigated compounds, as well as of imidazo[5,1,2-de]naphtho[1,8-ab]quinolizine, 12 is very low fluorescence quantum yield. Nonradiative depopulation of the fluorescence emitting S 1 state proceeds either by internal conversion, S 1 -S 0 , and/or by intersystem crossing, Fig.…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, they typically possess high fluorescence quantum yields. [22][23][24][25][26][27][28] With the advent of interest in ladder-type aromatic heterocycles, 29,30 we reasoned that π-expanded imidazo[1,2-a]pyridines being analogues of recently explored systems such as indolo [3,2-b]indoles 31,32 can offer new opportunities once an efficient synthetic methodology is developed. Indolo[3,2-b]indoles (1), benzofuroindoles (2) and benzothioindoles (3) were recently reported as highly active sex steroid hormone receptor modulators 33 and anticancer agents ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…9 Recently we revealed that 3-(naphthalen-1-yl)-imidazo[1,2-a]pyridine can be synthesized from a singly-linked precursor by anion-radical coupling 10 in 63% yield. 11 Since anion-radical coupling is a relatively weakly studied reaction (Scheme 1), we wondered if this methodology can be expanded to its analogs possessing other aromatic units instead of naphthalene. This would allow us to study the relationship between the structure of substrates and the efficiency of this reaction.…”
Section: Introductionmentioning
confidence: 99%